Preliminary Test Estimation in the Rayleigh Distribution Using Minimax Regret Significance Levels - Baklizi, Ayman (Universiti Putra Malaysia Press, 2004)
Given a prior guess of the unknown parameter, the usual preliminary test estimator based on the maximum likelihood estimator for the Rayleigh scale parameter is developed. The optimal significance levels based on the minimax regret criterion and the corresponding critical values are numerically obtained.